A literature review: The use of Duolingo to develop verbal-linguistic intelligence in elementary school students - Khumaeroh, Siti; Yuliyanto, Aan; Rogibah, Rogibah; Fauzan, Ahmad; Noviyanto, Tommy; Rochim, Ahmad Abdul; Muslikha, Amelia; Nasikhah, Azizatun (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
Verbal linguistic intelligence is part of multiple intelligence, which must be developed early. This study explores using Duolingo to develop verbal-linguistic intelligence in learning English for elementary school students. This study was conducted through a literature study to describe the use of Duolingo based on the exposure of several experts and on supporting reference studies that have been carried out. Duolingo is a language learning application that can be accessed online, making it easier for students to learn English in the classroom and outside of learning activities. Duolingo has many easy-to-use features and is designed to be fun to learn. In the Duolingo application, there is a skill tree to describe each task to be carried out, such as understanding basic phrases, expressing common phrases, discussing food, naming animals, using plurals, expressing ownership, using object pronouns, discussing clothes, recognizing present verbs, naming color, ask questions and other skill trees. Based on the literature review conducted, it shows that Duolingo allows students to have more learning opportunities both online and offline. The characteristics of Duolingo that contain simple games can help students develop English linguistic verbal intelligence, including writing, reading, speaking, and listening skills, as well as vocabulary mastery.